Exclusion, Minimization, Inaction: A Critical Review of Ireland's Policy Response to Gender-Based Violence as It Affects Migrant Women - Reilly, Niamh; Sahraoui, Nina; McGarry, Orla (Frontiers in Human Dynamics, 2021)
Abstract: This critical review of Ireland’s policy response to gender-based violence as it affects migrant women contributes to recent literature that focuses on how states’ legal and policy regimes can be part of the problem, in this case adding to rather than reducing GBV related vulnerabilities experienced by migrant women. Through a review of key policy, law and NGO documents, the report foregrounds the significance of context-specific framing and interpretation of influential ideas in shaping the horizons of possible policy action. The review is contextualised in relation to developments in Ireland concerning migration, citizenship and ‘racism' and racialisation and more broadly vis-a-vis literature in the nexus of migration governance and gender based violence. The authors trace the development of dominant ideas that shape policy practice with a focus on their interpretation in the Irish context − namely, vulnerability, intersectionality and interculturalism. Four particular areas of policy response are identified, which reveal a pattern of policy failure on the part of the Irish state characterised by exclusion, minimisation and/or inaction. These relate to assessment of vulnerability of applicants for international protection; addressing gender-based violence in the context of direct provision accommodation; identification and referral of trafficking victims; and response to domestic violence linked to dependent migration status. The authors find that the pattern of failure identified is linked to the current dominance of an ever narrowing and individualised framing of vulnerability found in EU migration regulations, a lack of application of an intersectional gender perspective, the diminished influence of indivisible human rights norms requiring attention to economic, social and cultural rights, as a well as a wider national context of declining resource allocation to addressing gender-based violence and integration including anti-racism initiatives for over a decade.